Tingkat Kepuasan Pasien Rawat Jalan di Klinik Delima Sehat Menggunakan Model SERVQUAL - Rizqulloh, Lutfiyah; Artati, Diah Kari (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
Delima Sehat Clinic in Semarang has become one of the healthcare facilities with the highest number of BPJS participants in the city and has experienced an increase in patient visits. However, patient dissatisfaction remains regarding waiting times, referral procedures, staff attitudes, and limited parking space. This study aimed to evaluate patient satisfaction with the services provided and to identify the SERVQUAL dimension with the most significant influence on the healthcare service process. A cross-sectional study design with a descriptive method was used. The sample consisted of 80 outpatients selected through accidental sampling. Data were collected using a validated SERVQUAL questionnaire with a four-point Likert scale. Descriptive statistics were employed for data analysis. The assurance dimension showed the highest satisfaction level (76.25%) with an average score of 3.88±0.33, while the tangibles dimension recorded the lowest satisfaction (36.25%) with an average score of 3.69±0.50. Overall, patient satisfaction reached 78.75% with an average score of 3.90±0.30. It is recommended that clinic management pay closer attention and make improvements particularly in the tangibles dimension, such as expanding the waiting area and enhancing the comfort of facilities, while continuing to maintain the quality of other service dimensions.